The Effect of Viral Marketing Technologies on Consumer Behavior _ A survey of a sample of students from the college of administration and economics - حمودي عبد الله هاشم; ايوب زيد فوزي; خميس عبدالله عبد الحق (Journal of Economics and Administrative Sciences, 2019)
Abstract: Viral marketing has become one of the modern strategies adopted by organizations in the marketing of products and services. The idea of viral marketing focuses on the social relations between individuals and groups. As a result of the technological development, most organizations have resorted to using the Internet and its applications and social media to market and promote their products. To reach the largest number of consumers to display their products and services in many ways, including text, audio, visual or video and thus affect the behavior of the consumer. The problem of the study was the following question (do viral marketing technologies have an impact on consumer behavior?) The objective of the study is to identify the respondents’ views on their acceptance of viral marketing techniques and their impact on their behavior. To achieve the objectives of the study (294) questionnaires were distributed to a sample of students of the college of Administration and Economics as users of the Internet and its applications (Web Site, E-mail, Facebook, YouTube and Viber) on the one hand, and consumers as well. In order to test the hypothesis of the main study, which states that (there is no statistically significant correlation between viral marketing techniques and consumer behavior) and its hypotheses, the data were analyzed statistically using Minitab. The results of the study were statistically significant and found that there was a positive correlation between the study variables. The results of the study showed that there is a significant positive effect of the removal of viral marketing techniques on the behavior of the consumer in the sample of the study, except for Viber technology, it does not affect consumer behavior. Organizations that use different technologies to introduce their products have a positive impact on consumer behavior.